Effects of Embodied Interaction on Reading Comprehension in a Multimodal Environment (International Conference on Computers in Education, 2016)
The study examined the effects of embodied interaction on reading comprehension in a multimodal environment. Specifically, this study compared how textual, visual or gestural modes affect young children’s reading comprehension. 91 Chinese EFL learners were assigned to one of the three modes to complete a reading task. During the reading task, they made several predictions by selecting a text description, selecting a picture or doing gestures that best match their predictions. Results showed that the three modes led to comparable level of reading comprehension. However, when reading ability was taken into account, the high level readers’ comprehension was negatively affected by the gesture mode while the low level readers’ comprehension was not. The findings suggest that visuals and gestures can be integrated into a multimodal reading environment to make reading an active learning experience. However, in designing an interactive digital storybook involving gestures, it is recommended that individual differences in reading ability be addressed to maximize its effect. Suggestions for future studies are discussed.